La relación del empowerment psicológico y el engagement laboral en colaboradores de empresas del sector privado - Pons Muzzo Vizcarra, Andrea (2021)
The organizational context, through new challenges, is taking actions with the purpose of generating positive impacts on people's well-being and on the company's results. Based on this, psychological empowerment, an intrinsic motivational construct (Spreitzer, 2007), takes a relevant role together with work engagement, considered as a positive state at work (Schaufeli & Bakker, 2010) based on the DRL Model for its development. The present study aims to identify the relationship between psychological empowerment and work engagement in employees of private companies. A systematic search review was carried out based on the PRISMA guide (Urrútia & Bonfill, 2010) in the Scopus, EBSCOhost, Proquest and ScienceDirect databases. Nine studies that met the determined criteria were analyzed. The results indicated that there is a direct positive relationship between both variables, as well as, based on other models, they play positive mediating and predictive roles with resources such as leadership, job satisfaction and organizational trust. These findings suggest that enhancing intrinsic motivation including autonomy, self-determination, influence and identity promote a state of well-being and fulfillment within the work role.